Moderation of Learning Motivation on the Effectiveness of Problem-Based Learning on Elementary School Students' Science Literacy: Quasi-Experimental Pretest–Posttest - Rina Astuti; Adhi Susilo; Rai Bagus Triadi (Postgraduate, University of Mataram, 2026)
This research is motivated by the importance of scientific literacy at the elementary school level and the need for an effective learning model to improve it, by considering students' psychological factors such as learning motivation. Objective: This study aims to investigate the effect of Problem-Based Learning (PBL) and learning motivation on elementary school students' scientific literacy, and to test the interaction between the two variables. Method: This study used a quasi-experimental design with a pretest–posttest nonequivalent control group. The sample consisted of 60 fourth-grade students at Mekar Bakti Public Elementary School, Indonesia, divided into two classes (n=30 each). Scientific literacy was measured using a PISA-oriented essay test (scale 0–100), while learning motivation was assessed with a 40-item Likert questionnaire (α=0.884). Data were analyzed using a 2×2 factorial ANOVA and Tukey HSD follow-up test. The findings showed that: Students in the PBL class achieved higher scientific literacy than those in the conventional class (M=78.63 vs 68.57; p=0.001); Students with high motivation outperformed students with low motivation (M=76.67 vs 70.53; p=0.039); There was a significant interaction between PBL and learning motivation (F (1.56) =17.23; p<0.001); The post-hoc test results showed that the PBL-high motivation group performed significantly better than the other three groups. These findings indicate that the PBL model is most effective when student motivation is high.